Factors considered by engineers with regard to geographical location - Hoffman, Josias Matthiam (My University, 2013)
Corporations traditionally make decisions regarding their geographical location considering business (natural resources, policy, tax, etc.), infrastructure (technology, housing, transportation, etc.) and labour (literacy, etc.) attributes. However, present-day, technology-oriented organisations attempt to better accommodate the needs of their employees when choosing the organisation’s geographical location. This research sets out to identify the factors considered by professionals in first world countries that support or undermine their choice of geographical location, and to further establish the relative utility of these factors to engineers in the South African petrochemical industry. This research uses a conjoint analysis to assess respondents’ preference to certain profiles – consisting of various levels of attributes – in order to determine the relative utility and importance of each attribute. Respondents were requested to rank-order the profiles from least to most preferred, as well as provide certain demographic information. The research found social structures to be the attribute with highest importance, twice that of financial remuneration; professional opportunities; and support structures (all carrying equal importance). Professional association was deemed least important. The research further found that all respondents equally preferred high financial remuneration, but were prepared to trade this attribute with other attributes. Similarly, respondents (particularly older respondents) were also prepared to trade professional opportunities for other attributes. Younger respondents valued the utility professional association more than the aggregate. The research also revealed that female respondents (compared to their male counterparts), and single respondents (compared to married respondents), were more prepared to ii sacrifice support structures for other attributes. All respondents preferred good social structures with regard to their geographical location. The research showed that employers can consider above market related financial remuneration as an incentive to attain or retain employees, but that it is not absolute, as other factors weigh equal (and more) in the employees’ utility perception. In addition, the research indicated that employers should consider the utility of professional opportunities for employees as a motivating attribute, but that this utility tapers off for their older employees. It also came to light that the professional association utility is particularly valued among younger employees. Furthermore, it became apparent that, although female and single employees would sacrifice supportive support structures, both demographics changed their perceived utility when they get married. Lastly, the study revealed that employees unanimously assign high value to a geographical location where good entertainment, quality of life and work–life balance is perceived.
MBA thesis
Keywords: Engineers; Employment location